Implementasi Good Governance Dan Perizinan Dalam Pemanfaatan Ruang Di Indonesia - Romi ' (Fakultas Hukum Universitas Riau, 2011)
The Spatial planning is government domain, because its related to the government as much as the basic need of people who have been mandated by the constitution. There are at least two reasons that reinforce these arguments, the first spatial planning is very influential on the national investment climate. And second, unintegrated spatial planning can lead to conflict horizontally on a practical level. The problem of its paper are how arrangement of spatial planning permission in Indonesia and whether good governance principles are accommodated in spatial planning regulation in Indonesia. In practice, implementation of permission in the use of space in Indonesia has yet to be implemented to the maximum. The main factor cause is due to the unavailability of regional spatial plan of local regulations (Perda RTRW) as the main parachute control utilization of space in the area. Meanwhile, related to the implementation of the principles of good governance, at least the Spatial Planning Act has been to accommodate the four principles, namely principles of accountability, transparency principle, the principle of participation and the principle of legal certainty.